Design of experiments optimization of fluorine-doped tin oxide films prepared by spray pyrolysis for photovoltaic applications. Issue 8 (15th April 2023) - Pinheiro, X.L.; Vilanova, A.; Mesquita, D.; Monteiro, M.; Eriksson, J.A.M.; Barbosa, J.R.S.; Matos, C.; Oliveira, A.J.N.; Oliveira, K.; Capitão, J.; Loureiro, E.; Fernandes, P.A.; et al.
Abstract: Transparent conducting oxides (TCOs) have witnessed an ever-expanding use in our lives through many optoelectronic applications, namely photovoltaic (PV) devices. Indium-tin oxide (ITO) is the most used and studied TCO, but it lacks thermal and chemical stability and indium is a scarce and toxic element. Fluorine-doped tin oxide (FTO) emerged as the most promising alternative to ITO, presenting better thermal and chemical stability. Among the numerous techniques for depositing FTO thin films over glass substrates, spray pyrolysis is the simplest and most economical, with great potential for upscaling. However, the relative importance of the experimental variables that influence the optoelectronic properties remains barely addressed. Following this premise, the present work aimed at optimizing the deposition of FTO films on soda lime glass (SLG) substrates by spray pyrolysis following a Design of Experiments (DoE) methodology. The optoelectronic properties of FTO-SLG substrates was evaluated based on their optical transmittance and sheet resistance, both combined in a figure of merit (FoM) tailored for PV applications. It was concluded that the volume of sprayed solution and the fluorine/tin ratio in the precursor have the greatest influence in the FoM, being the optimal deposition conditions a sprayed volume of 60.8 ml and a [F]/[Sn] ratio of 0.45. FTO-SLG substrates prepared with these conditions achieved a FoM of 0.680 Ω□ − 1/10, corresponding to a sheet resistance of 3.40 Ω□ and a transmittance equivalent to 77% of the maximum current generated in the considered spectrum. The improved FoM was validated in dye-sensitized and perovskite solar cells (DSSCs and PSCs, respectively), assembled with in-house optimized and commercial substrates. The efficiency of DSSCs was improved by 8.9% (relative), whereas PSCs achieved a light-to-power efficiency of 17% (absolute), corresponding to an improvement of 4.7% (relative).